Bioefficacy of Bio-insecticide from Chromolaena odorata (L.) R. M. King & H. E. Robins Methanol Extract against Brown Planthopper, Nilaparvata lugens (Stål.) - Mohd Zaki, Nor Ilya; Asib, Norhayu; Shari, Erwan Shah; Ahmad-Hamdani, Muhammad Saiful (Penerbit UPM, 2024)
The rice brown planthopper (BPH), Nilaparvata lugens (Stål.) is a highly damaginginsect pest to rice crops. The excessive use of synthetic chemicals has resulted in the development of resistance to insecticides and negative consequences for the environment andinsect biodiversity. Hence, three common weed species, namely Ageratumconyzoides, Chromolaena odorata, and Mallotus paniculatus were evaluated on the comparativeextraction yield in different solvents, as well as the toxicity potential in the selected methanol extract. Further, the bioactive compounds in C. odorata were characterised and potential bioinsecticide formulations were developed and evaluated on the BPH..Methanol extract displayed higher efficiency, yielding 17.29% as compared to only 3.19%in hexane extract. Insecticidal activity evaluation demonstrated that C. odorata exhibited the highest toxicity(77.5% at 10,000 ppm), having LC50 value of 977 ppm, while A. conyzoides (55.2%at 10,000ppm) and M. paniculatus (60.0% at 12,000 ppm) produced LC50 values of 6549 ppmand21,940 ppm, respectively. Subsequently, a plant-based bio-insecticide was formulatedusingthe crude methanol extract of C. odorata as active ingredient. A mixture of surfactant (Emersense® AM8025), oil (Palm Kernel Oil Ester), and water had resulted a stablemacroemulsion called EM-PKOE. The formulated macroemulsion displayed enhancedtoxicity and efficacy against BPH nymphs, with LC50 value of 220 ppm, outperformingtheunformulated crude methanol extract (977 ppm). Chemical composition analysis usingGas-Chromatography-Mass Spectrometry (GC-MS) revealed that C. odorata primarily containedsesquiterpenes (24.14%). This study proposes C. odorata as a potential bio-insecticideforBPH combatant, necessitating further research on formulation for eventual commercializationto sustainable BPH control in rice cultivation.